IMPROVEMENT OF MEDICAL CARE FOR THE PATIENTS WITH LIPID DISORDERS (CASE OF LIPID CENTER OF THE “DISTRICT CARDIOLOGICAL DISPENSARY “CENTER FOR DIAGNOSTICS AND CARDIOVASCULAR SURGERY”, SURGUT CITY) - K. G. Kozhokar; I. A. Urvantseva (Российский кардиологический журнал, 2017)
Lipid metabolism disorders are regarded as a significant factor of cardiovascular diseases pathogenesis that are associated with atherosclerosis, and cardiovascular death event. It is feasible to realize the project on establishing of regional lipid centers with aim of increased efficacy of patients treatment, with cardiovascular diseases and decrease of morbidity and mortality from cardiovascular diseases inRussian Federation.Aim. The aim of the Lipid center functioning — increased availability of highqualified cardiological and angioneurological care of patients with lipid metabolism disorder, and increase of efficacy of cardiovascular patient’s management.Material and methods. Lipid center of the KMAD-Yugra “CDCVS” has been established on the functional basis, at the consulting cardiological unit in January 2016. The tasks of the Center: diagnostics, treatment and follow-up of patients with complicated lipid disorders (incl. inherited), angioneurological pathology; conduction of federal registry of the familial hypercholesterolemia (FHCE) and other rare lipid metabolism disorders; education of clinicians and nurses; interaction with the authorities and patient societies.Results. Based upon the data ofLipidCenter, there are 2 registries ongoing: registry of a dynamical follow-up for angiology (regional); registry of FHCE (state level). Into the Russian FHCE registry, 30 patients included during a year, and into dynamic angioobservation — 318 patients. Taken high prevalence of the pathology in younger patients, we have developed and implemented an algorithm of the young acute coronary syndrome patients follow-up; developed and approved the algorithms of interaction of the in-patient and outpatient parts of specialized care for lipid disorder patients.Conclusion. Based on a year experience of the Lipid Center KMAD-Yugra “CDCVS” it is plausible to say that an implementation into the structure of medical institutions such departments among Russian Federation, makes it to establish effective organization of diagnostics and treatment of patients with lipid metabolism disorders, and is evidently clinically effective and economically expedient.